William McKinley--Encyclopedia of Presidents - Kent, Zachary (Chicago, IL: Childrens Press, 1989)
Summary: Presents the early life, military career, and political life of the president who was assassinated in 1901 during his second term in office.
Keywords: McKinley, William--1843-1901.; Presidents